Relationships between gastrointestinal permeability, heat stress, and milk production in lactating dairy cows - M.D. Ellett; R.P. Rhoads; M.D. Hanigan; B.A. Corl; G. Perez-Hernandez; C.L.M. Parsons; L.H. Baumgard; K.M. Daniels (Journal of Dairy Science, 2024)
ABSTRACT: Heat stress (HS) is a global issue that decreases farm profits and compromises animal welfare. To distinguish between the direct and indirect effects of HS, 16 multiparous Holstein cows approximately 100 DIM were assigned to one of 2 treatments: pair fed to match HS cow intake, housed in thermoneutral conditions (PFTN, n = 8) or cyclical HS (n = 8). All cows were subjected to 2 experimental periods. Period 1 consisted of a 4 d thermoneutral period with ad libitum intake. During period 2 (P2), the HS cows were housed in cyclical HS conditions with a temperature-humidity index (THI) ranging from 76 to 80 and the PFTN cows were exposed to a constant THI of 64 for 4 d. Dry matter intake of the PFTN cows was intake matched to the HS cows. Milk yield, milk composition, rectal temperature, and respiration rate were recorded twice daily, blood was collected daily via a jugular catheter, and cows were fed twice daily. On d 3 of each period, Cr-EDTA and sucralose were orally administered and recovered via 24 h total urine collection to assess gastrointestinal permeability. All data were analyzed using the GLIMMIX procedure in SAS. The daily data collected in P1 was averaged and used as a covariate if deemed significant in the model. Heat stress decreased voluntary feed intake by 35% and increased rectal temperature and respiration rate (38.4°C vs. 39.4°C and 40 vs. 71 respirations/min, respectively). Heat stress reduced DMI by 35%, which accounted for 66% of the decrease in milk yield. The yields, and not concentrations, of milk protein, fat, and other solids were lower in the HS cows on d 4 of P2. Milk urea nitrogen was higher and plasma urea nitrogen tended to be higher on d 3 and d 4 of HS. Glucose was 7% lower in the HS cows and insulin was 71% higher in the HS cows than the PFTN cows on d 4 of P2. No difference in lipopolysaccharide-binding protein was observed. Heat stress cows produced 7 L/d more urine than PFTN cows. No differences were detected in the urine concentration or percentage of the oral dose recovered for Cr-EDTA or sucralose. In conclusion, HS was responsible for 34% of the reduction of milk yield. The elevated MUN and the tendency for elevated plasma urea nitrogen indicate a whole-body shift in nitrogen metabolism. No differences in gastrointestinal permeability or lipopolysaccharide-binding protein were observed. These results indicate that, under the conditions of this experiment, activation of the immune system by gut-derived lipopolysaccharide was not responsible for the decreased milk yield observed during HS.